2019
DOI: 10.1002/art.40766
|View full text |Cite
|
Sign up to set email alerts
|

Dampening of CD8+ T Cell Response by B Cell Depletion Therapy in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: Objective. To compare the effects of rituximab (RTX) and conventional immunosuppressants (CIs) on CD4+ T cells, Treg cells, and CD8+ T cells in antineutrophil cytoplasmic antibody-associated vasculitis (AAV).Methods. A thorough immunophenotype analysis of CD4+, Treg, and CD8+ cells from 51 patients with AAV was performed. The production of cytokines and chemokines by CD8+ T cells stimulated in vitro was assessed using a multiplex immunoassay. The impact of AAV B cells on CD8+ T cell response was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…This is additionally applicable to disease settings in which limiting the function of CD8 T cells by depleting B cells may be beneficial. Rituximab use in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) alters the CD8 T cell memory compartment, reducing the frequency of effector memory cells re-expressing CD45RA (TEMRA) ( Néel et al, 2019 ). B cells isolated from these patients increased the cytokine output of CD8 T cells in ex vivo co-cultures, providing evidence for a direct, positive effect of B cells on CD8 T cells in this disease setting, where CD8 T cells are pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…This is additionally applicable to disease settings in which limiting the function of CD8 T cells by depleting B cells may be beneficial. Rituximab use in patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV) alters the CD8 T cell memory compartment, reducing the frequency of effector memory cells re-expressing CD45RA (TEMRA) ( Néel et al, 2019 ). B cells isolated from these patients increased the cytokine output of CD8 T cells in ex vivo co-cultures, providing evidence for a direct, positive effect of B cells on CD8 T cells in this disease setting, where CD8 T cells are pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one study in AAV found that whereas rituximab treatment did not affect CD4+ and Treg frequencies, it was associated with reduced CD8+ T EMRA frequencies and circulating chemokine and cytokine levels. Interestingly, co-cultures of CD8+ T cells and autologous B cells from AAV patients resulted in enhanced production of proinflammatory cytokines indicating a pathogenic crosstalk between B cells and CD8+ T cells ( 117 ).…”
Section: Discussionmentioning
confidence: 99%
“… 8 6) As opposed to depleting T cells with cyclophosphamide, rituximab can disrupt the pathogenic B cell/CD8+ T cell axis, leading to a reduction in T cell cytokine production and subsequently less renal endothelial damage without hindering CPI antitumor activity. 39 40 In addition, the malignancy risk was reported to be lower in rituximab-treated ANCA-associated vasculitis patients than in cyclophosphamide-treated patients. 41 42 …”
Section: Discussionmentioning
confidence: 99%